Astrofísica & cosmologia no ensino de física: uma proposta de ensino para a abordagem de buracos negros no ensino médio - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
Black holes are one of the most intriguing phenomena in modern physics. Incorporating them into basic education not only sparks students' curiosity but also serves as an excellent platform to teach various scientific concepts. They allow for the exploration of gravity, general relativity, thermodynamics, and other areas. Additionally, discussing Black Holes helps students learn about the importance of the scientific method and develop critical analytical and interdisciplinary thinking skills. Incorporating such complex and fascinating topics into the school curriculum certainly enriches learning and inspires future generations of scientists. This work aims to explore the topic of Black Holes in the context of high school education, providing teachers with methodological and interactive tools to address this fascinating topic of Astronomy and Astrophysics in the classroom. The research is based on a wide range of scientific and educational references, aiming to integrate theoretical concepts with innovative pedagogical practices. To this end, we chose field research of a qualitative and quantitative-descriptive type. The data were obtained through a questionnaire using virtual resources such as Kahoot, with the participation of (number of students). The results were promising, indicating high content retention. This means that the use of the presented methods, along with the evolutionary sequence of the content, significantly contributed to the students' learning. The proposed activities not only facilitated the understanding of concepts related to Stars and Black Holes but also sparked a greater interest in this subject. The final considerations highlight the importance of continuing to investigate innovative methodologies for science teaching, especially in complex topics such as Astrophysics. It is recommended that teachers receive continuous training and that schools provide adequate resources for the implementation of these pedagogical practices.
Keywords: Buracos Negros; Ensino Médio; Astronomia; Astrofísica; Metodologias Interativas; Educação Científica; Ensino de Física; CNPQ:: CIÊNCIAS EXATAS E DA TERRA